Dual mobility cups in primary total hip arthroplasties: trend over time in use, patient characteristics, and mid-term revision in 3,038 cases in the Dutch Arthroplasty Register (2007–2016) - Bloemheuvel, Esther M; van Steenbergen, Liza N; Swierstra, Bart A (Acta Orthopaedica, 2018)
Background and purpose — We noticed an increased use of dual mobility cups (DMC) in primary total hip arthroplasty (THA) despite limited knowledge of implant longevity. Therefore, we determined the trend over time and midterm cup revision rates of DMC compared with unipolar cups (UC) in primary THA. Patients and methods — All primary THA registered in the Dutch Arthroplasty Register (LROI) during 2007–2016 were included (n = 215,953) and divided into 2 groups — DMC THA (n = 3,038) and UC THA (n = 212,915). Crude competing risk and multivariable Cox regression analyses were performed with cup revision for any reason as primary endpoint. Adjustments were made for sex, age, diagnosis at primary THA, previous operation, ASA score, type of fixation, surgical approach, and femoral head size. Results — The proportion of primary DMC THA increased from 0.8% (n = 184) in 2010 to 2.6% (n = 740) in 2016. Patients who underwent DMC THA more often had a previous operation on the affected hip, a higher ASA score, and the diagnosis acute fracture or late posttraumatic status compared with the UC THA group. Overall 5-year cup revision rate was 1.5% (95% CI 1.0–2.3) for DMC and 1.4% (CI 1.3–1.4) for UC THA. Stratified analyses for patient characteristics showed no differences in cup revision rates between the 2 groups. Multivariable regression analyses showed no statistically significantly increased risk for revision for DMC THA (HR 0.9 [0.6–1.2]). Interpretation — The use of primary DMC THA increased with differences in patient characteristics. The 5-year cup revision rates for DMC THA and UC THA were comparable.